(untitled) (Journal of Medicine, 2017)
Musculoskeletal pathology is common in primary care, but not always have a trivial origin. According to the symptoms and comorbidities of the patient, these pathologies have to make us think if is possible to be a guiding symptom of a more severe pathology. That is why we present the case of a young woman with cardiovascular risk factors (hypertension, smoking, obesity and sleep apnea-hypopnea syndrome) with pain at left trapezius and motor and sensory clinical alterations in left upper extremity. These comorbidities have in common their relationship with cerebrovascular pathology so, given the concomitant clinical musculoskeletal, we need to suspect this cause, as was in this case. J MEDICINE July 2017; 18 (2) : 113-114